'O flagrante ganha voz?': os significados da presença da pessoa presa nas audiências de custódia no estado de São Paulo - Toledo, Fabio Lopes (2019)
Since the year 2015 the Brazilian criminal justice started to rely on the custody hearing, a mechanism engineered to allow the presentation of any person detained by the police (in flagrante arrest) before a judge, responsible for interviewing the detainee within twenty-four hours after the detention is reported. This interview must embrace different issues, such as circumstances related to the arrest, torture or mistreatment during the police engagement, or even clarify doubts concerning personal matters. As the custody hearings were introduced, the judge´s decision regarding the maintenance of the detention, which used to be based solely on information registered in documents, can now rely on the prompt in-person judicial review of the arrest. Our study represents an effort to better understand the meanings of the detainee´s presence. In order to do so, we have decided to undertake a qualitative research, followed by a mainly inductive bias. To obtain the data, our study relies on two different techniques: semi-structured interviews with judges from different cities in the State of São Paulo and participant observation.